2018
DOI: 10.1002/hsr2.46
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis‐related practice patterns among hemodialysis patients with cancer

Abstract: Rationale, aims, and objectivesWith the achievement of longevity in hemodialysis patients, the risk of comorbid cancer has begun to draw attention. In the present study, we examined dialysis‐related practice patterns and compared those patterns by cancer status.MethodsUsing data from the Japan Dialysis Outcomes and Practice Patterns Study phase 4, we evaluated 2153 hemodialysis patients. Baseline cancer status for patients was separated into 3 categories: no cancer, cancer with recent treatment, and cancer wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…54 Despite these recommendations, real-world studies suggest that the use of ESA and iron is common among patients with ESKD and cancer, with dosing trends being similar to or higher than those observed among patients on hemodialysis without cancer. 55,56 In a US study of patients on hemodialysis with a cancer diagnosis, quarterly ESA use ranged from 94.1% of patients in 2002 to 90.0% in 2011, whereas epoetin alfa use decreased between 2002 (94.1%) and 2007 (85.4%) and remained stable thereafter. 55 In this study, monthly mean epoetin alfa doses initially increased from 66,000 to 83,000 IU between 2001 and 2004, then decreased to 52,000 IU by 2011, and were higher in patients with hematologic cancer than in those with solid tumors.…”
Section: Management Of Anemia Of Ckd In Patients With Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…54 Despite these recommendations, real-world studies suggest that the use of ESA and iron is common among patients with ESKD and cancer, with dosing trends being similar to or higher than those observed among patients on hemodialysis without cancer. 55,56 In a US study of patients on hemodialysis with a cancer diagnosis, quarterly ESA use ranged from 94.1% of patients in 2002 to 90.0% in 2011, whereas epoetin alfa use decreased between 2002 (94.1%) and 2007 (85.4%) and remained stable thereafter. 55 In this study, monthly mean epoetin alfa doses initially increased from 66,000 to 83,000 IU between 2001 and 2004, then decreased to 52,000 IU by 2011, and were higher in patients with hematologic cancer than in those with solid tumors.…”
Section: Management Of Anemia Of Ckd In Patients With Cancermentioning
confidence: 99%
“…55 A Japanese study of patients on hemodialysis also found that mean ESA doses were higher in those with cancer versus those without cancer (adjusted mean difference, 5.4 Â 10 3 IU/l/mo). 56 In our experience, the management of anemia in patients with ESKD and a history of cancer must weigh the risks of treatment against the alternative of chronic anemia and/or frequent RBC transfusions.…”
Section: Management Of Anemia Of Ckd In Patients With Cancermentioning
confidence: 99%